The hardware hacking handbook : breaking embedded security with hardware attacks - Woudenberg, Jasper van; O'Flynn, Colin (No Starch Press, 2022)
"A deep dive into hardware attacks on embedded systems explained by experts in the field through real-life examples and hands-on labs. Topics include the embedded system threat model, hardware interfaces, various side-channel and fault injection attacks, and voltage and clock glitching"--